2003
DOI: 10.1046/j.1439-0434.2003.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oligosaccharide and Spores from Aspergillus niger on the Defence Responses of Taxus chinensis Leaves In vitro

Abstract: Spores and oligosaccharide of a strain of Aspergillus niger, which had been isolated from the inner bark of Taxus chinensis, were used to treat T. chinensis leaves. The spores decreased the dry weight and chlorophyll content of the leaves, but increased their malondialdehyde content; oligosaccharide induced similar but more moderate changes. The changes in soluble protein, phenolic content, and peroxidase and phenylalanine ammonia‐lyase activity were also analysed. Oligosaccharide significantly increased all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Phenylalanine ammonia lyase was extracted and its activity determined by the modified methods of Li et al (2003). Fresh cells (0.5 g) were homogenized with quartz sand, 10 mL extraction buffer (0.1 m sodium borate, pH 8.0, 5 mm mercaptoethanol) and 0.5 g polyvinylpyrrolidone (PVP).…”
Section: Pal Activity Assaymentioning
confidence: 99%
“…Phenylalanine ammonia lyase was extracted and its activity determined by the modified methods of Li et al (2003). Fresh cells (0.5 g) were homogenized with quartz sand, 10 mL extraction buffer (0.1 m sodium borate, pH 8.0, 5 mm mercaptoethanol) and 0.5 g polyvinylpyrrolidone (PVP).…”
Section: Pal Activity Assaymentioning
confidence: 99%
“…CO 2 was entrapped in 2 M KOH and radioactivity counted in a scintillation counter (Beckman LS 6500, Milano, Italia). PAL (EC 4.3.1.5) activity was measured as described by Li et al [2003] with minor modifications. Leaf samples (0.5 g) were ground in a pre-frozen mortar with liquid nitrogen 2.5 ml extraction buffer (0.1 M sodium borate, pH 8.0, containing 5 mM mercaptoethanol).…”
Section: Experimental Designmentioning
confidence: 99%
“…Other molecules classified as elicitors are also capable of initiating a defence response in the host plant. These molecules are mostly oligosaccharides released by the pathogen or plant cells [6]. Studies have shown the action of oligosaccharides in the case of plant/fungus interaction.…”
Section: Introductionmentioning
confidence: 99%